Pengaruh Ovariektomi terhadap Kadar Estradiol dalam Darah Tikus (Rattus novergicus) Model Menopause - Dwi Yuliawati; Wuri Widi Astuti; Fitri Yuniarti (STIKES Karya Husada Kediri, 2019)
Menopause is a transition from previously productive to slowly to non-productive periods caused by the reduction in the hormones estrogen and progesterone. The occurrence of cardiovascular problems (CVD) increases substantially at menopause, as does atherosclerosis. Research using animal models of menopause is needed to learn more about the effects of menopause including the potential for atherosclerosis. Artificial methods of menopause with ovariectomy are expected to eliminate the source of estrogen. The aim of the study was to obtain preliminary animal models of menopause in terms decreased levels of estradiol in the blood of rats (Rattus novergicus) ovariectomy. The study design used a post-test only control group design, carried out in vivo using female rats (Rattus novergicus) Wistar strains of 25 rats randomly divided into 5 groups (negative, positive and 3 treatment controls). Ovariectomy was performed in the positive control and treatment groups. Estradiol levels were examined 30 days post ovariectomy in all groups. Estradiol test uses the ELISA method. Anova test results with a significance level of α = 0.05 established that the p value of 0,000 was less than α = 0.05 which means that there was a significant influence of ovariectomy on decreasing estradiol levels in rat blood (Rattus novergicus). From the results of the Post Hoc Tukey test it was found that of the 5 groups, the most different estradiol content was in the unovariectomy group of rats. Ovariectomy results can be used as an artificial method of menopause in rats (Rattus novergicus) in terms of decreased levels of estradiol in rat blood.